Uso de enzimas como bioindicadores em solos com diferentes culturas no Cerrado goiano - Zago, Leciana de Menezes Sousa (2016)
The Brazilian Cerrado covers about two million square kilometers with an area of low slope and well-drained soils, representing an attractive place for mechanized agriculture. The production of sugarcane, soybeans and corn in the state of Goiás have demanded the replacement of Cerrado areas in agricultural ecosystems. Despite the financial benefits, the use and soil management input changes in physical, chemical, biological and biochemical soil properties and consequently in its functional dynamic. That is on dependence of the transformation of organic matter mediated by microorganisms and extracellular enzymes. In the present study, we tryed to understand the influence of annual and perennial crops on the activity of enzymes that participate in the carbon cycle, nitrogen and phosphorus and propose the use of hydrolases as soil quality bioindicators. Cerrado native soil samples and in soy, corn and sugarcane were collected at a depth of 0-10 cm during periods of rain and drought in six points in the state of Goiás. We evaluated the levels of macronutrients, organic matter, total organic carbon, total nitrogen and carbon of microbial biomass, as well as the activity of α and β-glycosidases, acid phosphatase, protease and glycine aminopeptidase. Data were analyzed by ANOVA Two-way and MANOVA One-way and the means were compared by Tukey test and test T2 Hotteling, respectively, considering p <0.05. The relationship between the chemical and biochemical properties was determined by Pearson correlation analysis. The nutrient content did not differ among the different types of land use. However, the organic matter content, total organic carbon, total nitrogen and microbial biomass carbon found in smaller proportion in agricultural ecosystems to monocultures, reflected the negative effect of land use on the quality of this ecosystem. The α and β-glucosidase activities were lower only in soils with sugarcane cultivation in relation to the annual crops and native Cerrado, which show a positive effect of tillage techniques and crop rotation on the species of the annual cycle. Acid phosphatase activity was lower in the cultivated areas where there were added phosphate fertilizers. Aminopeptidase and protease were influenced by the quality of the protein residues present in the soil, and the aminopeptidase activity was higher in native Cerrado native soils, while protease was less in this ecosystem. Although the replacement of vegetation causes a loss of biodiversity and reduction of biochemical activity in the soil, the establishment of annual crops caused less impact on the ecosystem, since management practices stimulate microbial activity in the soil, which was not observed in relation to monocultures. Still, when all data were analyzed together it was possible to observe that the changes in vegetation cover and the management systems affected the biological activity in the soil. Thus, the variations found in hydrolase activities confirmed that these enzymes are sensitive to changes arising from land management and use practices and therefore can be used as soil quality bioindicators.